Impact of Diet-Modulated Butyrate Production on Intestinal Barrier Function and Inflammation - Bach Knudsen, Knud Erik (Nutrients, 2018)
A major challenge in affluent societies is the increase in disorders related to gut and metabolic health. Chronic over nutrition by unhealthy foods high in energy, fat, and sugar, and low in dietary fibre is a key environmental factor responsible for this development, which may cause local and systemic inflammation. A low intake of dietary fibre is a limiting factor for maintaining a viable and diverse microbiota and production of short-chain fatty acids in the gut. A suppressed production of butyrate is crucial, as this short-chain fatty acid (SCFA) can play a key role not only in colonic health and function but also at the systemic level. At both sites, the mode of action is through mediation of signalling pathways involving nuclear NF-κB and inhibition of histone deacetylase. The intake and composition of dietary fibre modulate production of butyrate in the large intestine. While butyrate production is easily adjustable it is more variable how it influences gut barrier function and inflammatory markers in the gut and periphery. The effect of butyrate seems generally to be more consistent and positive on inflammatory markers related to the gut than on inflammatory markers in the peripheral tissue. This discrepancy may be explained by differences in butyrate concentrations in the gut compared with the much lower concentration at more remote sites.